Вплив інноваційних процесів на розвиток сфери вищої юридичної освіти в Україні - Безпалова, О. І.; Bezpalova, O. I. (Legal education in modern university: project-bsaed approach to the work organization according to the guidelines of the European qualifications framework (experience of the paneuropean univercity) (March 22-24, 2017, Sladkovicovo, Slovak Repablic). – P. 15-18, 2017)
Окреслено проблеми, що стримують розвиток інноваційних процесів, у тому числі у сфері вищої юридичної освіти в Україні. Запропоновано шляхи вирішення вказаних проблем.

The problems that hinder the development of innovative processes, including in the field of higher legal education in Ukraine, are outlined. Ways to solve these problems are proposed.
Keywords: інноваційні процеси; вища юридична освіта; інноваційний розвиток; высшее юридическое образование; инновационные процессы; инновационное развитие; higher legal education; innovative processes; innovative development; publikatsii u zarubizhnomu vydanni